Effects of Gamma Irradiation on Microbiological Quality, Protein and Amino Acid Profile of Edible Bird Nest Powder - Sani, Norrakiah Abdullah; Yee, Ong Kuan; Ayob, Mohd Khan; Yasir, Muhammad Samudi; Babji, Abdul Salam; Ramli, Nazaruddin (Agriculture and Natural Resources, 2015)
The effect of gamma irradiation was determined on the microbiological quality and amino acid profile of edible bird nest (EBN) powder. Seven doses of irradiation were used: 0.0 (control), 1.0, 2.0, 5.0, 7.5, 10.0, 20.0 and 30.0 kGy. The total plate count (TPC) of EBN samples that were inhibited or had TPC < 100 colony forming units (CFU).g-1 at 20.0 kGy was determined. An irradiation dose of 5.0 kGy was required to reduce the coliform and Staphylococcus aureus counts to below 100 CFU.g-1 and the yeast and mold counts to below 1,000 CFU.g-1, while for Escherichia coli, 1.0 kGy was sufficient to inhibit or reduce the count to below 100 CFU.g-1. Salmonella spp. was not detected in any sample. A minimum irradiation dose of 20 kGy was required to sterilize the EBN powder samples most effectively. The pH and water activity values of the samples were in the ranges 8.34–8.90 and 0.621–0.674, respectively. The microbiological quality changes of irradiated samples were caused by the gamma irradiation alone. Gamma irradiation at doses as high as 10.0 and 20.0 kGy did not produce significant changes in the amino acid profiles of the EBN samples compared to the non-irradiated samples. Gamma irradiation improved the microbiological quality of the EBN samples without affecting their amino acid profiles.